Foreign Area Observations from Maidan. Issue 3 (2nd July 2016) - Harvey, James H.
ABSTRACT: The article consists of the author's observations while being assigned to the U.S. Embassy in Kyiv. The key points covered are the cause of the EuroMaidan Revolution, protester tactics, and a summary of the situation as of May 2014. It is written first-person and without citations.